Vitamin D and Glaucoma Risk: Current Evidence and Therapeutic Implications - Zarzycka, Marta; Lorek, Julia; Perski, Karol; Grzywna , Wojciech Piotr; Chrabąszcz , Joanna Małgorzata; Baltyzar , Konstancja Anna; Kurek , Maria Michalina; Polit-Różycka, Oliwia Kinga; Gadzalski, Krzysztof (Quality in Sport, 2026)
Introduction and purpose Glaucoma is a chronic, progressive optic neuropathy and a leading cause of irreversible blindness worldwide. Increasing evidence suggests that, beyond intraocular pressure, systemic and metabolic factors may contribute to its pathogenesis. Vitamin D, known for its immunomodulatory and neuroprotective properties, has emerged as a potential factor influencing glaucoma risk. The aim of this study was to evaluate the relationship between vitamin D supplementation and the risk of developing glaucoma. Material and method A narrative review of current literature, including experimental, observational, and clinical studies, was conducted to assess the association between vitamin D status, supplementation, and glaucoma-related outcomes such as intraocular pressure and optic nerve damage. Particular attention was given to studies analyzing serum 25(OH)D levels, supplementation patterns, and disease progression. Results Experimental studies indicate that calcitriol may reduce intraocular pressure and improve aqueous humor outflow, while observational studies often demonstrate an inverse relationship between serum vitamin D levels and glaucoma risk. However, clinical trials assessing supplementation have yielded inconclusive results, with some showing no significant effect on intraocular pressure. Variability in study design, population characteristics, and lack of detailed supplementation data limit the interpretation of findings. Additionally, vitamin D may exert neuroprotective effects independent of pressure regulation. Conclusions Vitamin D may play a supportive role in glaucoma prevention through systemic and ocular mechanisms however, current evidence is insufficient to confirm a clear protective effect of supplementation. Further large-scale, well-designed prospective studies are required to clarify its clinical significance.